Testing the EU fiscal surveillance : how sensitive is it to variations in output gap estimates - Langedijk, Sven.; Larch, Martin; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium: European Comission: Directorate-General for Economic and Financial Affairs, 2006)
Real-time estimates of the potential output are essential in the EU fiscal surveillance framework. They are used for the calculation of the cyclically-adjusted budget balance, one of the main indicators in the assessment of the fiscal performance of EU Member States. Our paper examines whether and how different degrees of smoothness of potential output would have supported different decisions in the EU budgetary surveillance in terms of both timing and substance. The results of our simulations show that, the accuracy of the diagnostic instruments especially those that measure the risk of breaching the 3% of GDP reference value of the Treaty is surprisingly robust. Only a very high and excessive degree of smoothing of potential output would significantly reduce the reliability of the surveillance indicators. In the light of our results a somewhat higher degree of smoothing compared with the current practice would not seem to be harmful for EU fiscal surveillance. During economic upturns it would guaranty a higher degree of caution by signalling larger and possibly longer periods of economic 'good times' which would in turn warrant more fiscal consolidation. Keywords: EU fiscal surveillance, potential output, output gap
Economic Papers